The cost and cost trajectory of whole‐genome analysis guiding treatment of patients with advanced cancers. Issue 3 (12th March 2017) - Weymann, Deirdre; Laskin, Janessa; Roscoe, Robyn; Schrader, Kasmintan A.; Chia, Stephen; Yip, Stephen; Cheung, Winson Y.; Gelmon, Karen A.; Karsan, Aly; Renouf, Daniel J.; Marra, Marco; Regier, Dean A.
Abstract: Background: Limited data exist on the real‐world costs of applying whole‐genome analysis (WGA) in a clinical setting. We estimated the costs of applying WGA to guide treatments for patients with advanced cancers and characterized how costs evolve over time. Methods: The setting is the British Columbia Cancer Agency Personalized OncoGenomics (POG) program in British Columbia, Canada. Cost data were obtained for patients who enrolled in the program from 2012 to 2015. We estimated mean WGA costs using bootstrapping. We applied time series analysis and produced 10‐year forecasts to determine when costs are expected to reach critical thresholds. Results: The mean cost of WGA over the study period was CDN34, 886 per patient (95% CI: 34, 051, 35, 721). Over time, WGA costs decreased, driven by a reduction in costs of sequencing. Yet, costs of other components of WGA increased. Forecasting showed WGA costs may not reach critical thresholds within the next 10 years. Conclusion: WGA costs decreased over the studied time horizon, but expenditures needed to realize WGA remain significant. Future research exploring costs and benefits of WGA‐guided cancer care are crucial to guide health policy. Abstract : Limited data exist on the real‐world costs of applying whole‐genome analysis in a clinical setting. We estimated the costs of applying whole‐genome analysis to guide treatments for patients with advanced cancers and characterized how costs evolve over time. Whole‐genome analysis costs decreased over the studied time horizon, but expenditures needed to realize whole‐genome analysis remain significant.